Percepções de Professores dos Anos Iniciais do Ensino Fundamental sobre Aspectos da sua Formação e Práticas para Ensinar Ciências - Camargo de Lima, João Paulo; Fabilele, Fabiele Cristiane Dias Broietti; Keila, Keila Padilha De Oliveira Camargo De Lima; Tamires, Tamires Bartazar Araújo (Góndola, enseñanza y aprendizaje de las ciencias, 2023)
In this article we seek to identify the perceptions of teachers who teach science in the early years of elementary school regarding aspects of their education and practices for teaching science at this educational level. A questionnaire was applied to eight teachers with questions about aspects of their initial teacher education, methodologies and teaching approaches; planning and organization of classes, as well as difficulties, doubts and challenges of their classroom practices, to teach Science. The teachers' answers were organized and interpreted following the assumptions of Content Analysis. Through the analyzes we found 3 categories: the perceptions about aspects of their training to teach Science; aspects related to the organization, planning and development of Science classes and the main difficulties and challenges faced by teachers in the exercise of teaching activity. Despite the difficulties and barriers encountered in teaching Science, the search for didactic resources and teaching strategies by teachers proved to be a potentiator to foster teacher training and professional development.